Synthesis, structural and optical properties of cobalt (II) doped zinc silicate via sol-gel method - Mohd Rasdi, Norhafizah (2017)
Zinc silicate (Zn2SiO4) has been distinguished as a competent host matrix for dopant transition and rare earth ion for efficient luminescence properties in red, green and blue spectral zones. The high demand of optical based materials for future development in light emitting diode (LED) and display panels has led to growing interest in producing Zn2SiO4 based glass ceramic via sol-gel method. In this researched work, the physical and optical properties of cobalt (II) doped zinc silicate were studied in detail. The sample was prepared by the sol-gel method at different compositions and heated at different heat treatments in the furnace. The preparation began with 2:1 mole ratio of Zn: SiO and with a different mole ratio of cobalt (II) doped (0, 1, 2, 3, 4 and 5 mol%) and the sample powder underwent heat treatment (600, 700, 800, 900 and 1000 °C) processes. The structural, morphological, and optical properties of cobalt (II) doped zinc silicate were studied in detail by using X-Ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), ultra-violet visible spectroscopy (UV-Vis), and photoluminescence spectroscopy (PL). XRD indicates that the formation of zinc oxide changes to zinc silicate (β-Zn2SiO4 and α- Zn2SiO4) as the sintering temperature increases from 600 to 1000 °C. Furthermore, as the dopant increases, the intensity of the sample also increases. This indicates that the crystallinity increases as the temperature and dopant increases. FESEM observation shows the average grain size increased with the increase of sintering temperature and when the dopant content increases the sample particle is more agglomerate and compact. The morphological properties show that the grain size of the samples increases as the heat treatment and dopant increases which leads to the increase in its growth rate. The FTIR result revealed the presence of Si-O-Si, ZnO4 and SiO4 vibrations in the sample. The UV-Vis study shows that, as the sintering temperature increase, the band gap energy tends to increase due to the improvement of the crystallinity and quantum size effect, while the decreasing band gap due to the separation energy of electron-hole pair. Meanwhile, as the dopant increases the band gap tends to decrease due to the involvement of non-bridging oxygen in the sample particle. The emission of photoluminescence spectra of cobalt doped zinc silicate powder after the sample was excited at a wavelength of 350 nm shows emission at 3 different peaks which were two blue emissions (420 and 480 nm) and green emission (525 nm). All peaks can be associated with d → d transition Co²⁺ from ⁴A₂ → ⁴T₁ (⁴P). In summary, it can be concluded that the sample of cobalt doped zinc silicate was successfully synthesized via sol-gel method and from the characterization, this shows that the sample can be suitable for optical devices.